Surface characterization of plasma-modified resist patterns by ToF-SIMS analysis - Park, Jong S.; Kim, Hyung-jun (ELSEVIER SCIENCE BV, 2009)
We report the use of the time-of-flight secondary ion mass spectrometry (ToF-SIMS) technique to determine whether the patterned bank is suitable for inkjet printing, by evaluating the phobicity contrast between two regions, the glass substrate inside pixels and the surface of the resist bank. We first examined the effect of plasma treatment on the ink spreading behavior inside pixels. The phobicity contrast was optimized by removing residues inside the pixels and by providing high phobicity on the bank surface. We show that ToF-SIMS spectra and mass-resolved images are effective tools in examining the existence of organic contaminants inside pixels and predicting the actual inkjet printing behavior. The ToF-SIMS technique will find promising applications that are related to surface characteristics where conventional contact angle measurement is hard to apply due to geometrical and technical restrictions. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: COLOR FILTER; ELECTRONICS; POLYMER; FILMS; INKS; ADHESION